Femtochemistry and femtobiology : ultrafast events in molecular science : VIth International Conference on Femtochemistry, Maison de la Chimie, Paris, France, July 6-10, 2003 - Martin, Monique M.; Hynes, James T. (Elsevier, 2004)
Details Femtochemistry and Femtobiology - a rapidly expanding area of science.